2015
DOI: 10.1118/1.4915544
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characterization of a microDiamond detector in clinical scanned carbon ion beams

Abstract: Purpose: To investigate for the first time the dosimetric properties of a new commercial synthetic diamond detector (PTW microDiamond) in high-energy scanned clinical carbon ion beams generated by a synchrotron at the CNAO facility. Methods: The detector response was evaluated in a water phantom with actively scanned carbon ion beams ranging from 115 to 380 MeV/u (30-250 mm Bragg peak depth in water). Homogeneous square fields of 3 × 3 and 6 × 6 cm 2 were used. Short-and medium-term (2 months) detector respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…), in which no LET dependence is observed. These conclusions are in agreement with previous experimental work obtained with a single microDiamond detector (SN 122030) . As for the microDiamond detector under‐response in carbon and oxygen beams, the authors believe that it could be explained in terms of certain recombination effects in the thin synthetic diamond layer due to the LET value.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…), in which no LET dependence is observed. These conclusions are in agreement with previous experimental work obtained with a single microDiamond detector (SN 122030) . As for the microDiamond detector under‐response in carbon and oxygen beams, the authors believe that it could be explained in terms of certain recombination effects in the thin synthetic diamond layer due to the LET value.…”
Section: Resultssupporting
confidence: 91%
“…The response of the PTW‐60019 microDiamond detector has been little investigated in carbon ion beams. A study by Marinelli et al indicates that the response of this type of detector exhibits no LET dependence, although this study was performed in high‐energy clinical beams, where the energy spread in the Bragg peak is large and small quenching effects would not be very apparent. In a second study, Rossomme et al observed a 20% relative under‐response of a PTW‐60019 microDiamond detector compared to that of a Markus ionization chamber, in the Bragg peak region of a 62 MeV/n carbon ion beam.…”
Section: Introductionmentioning
confidence: 95%
“…, the evaluation of four microDiamonds indicates that the microDiamond detectors are not reproducible and presented differences in terms of stability, sensitivity, and LET dependence. The LET dependence is in contrast with other studies . Evaluation of the LET dependence in scanned ion beams is rather time consuming compared to scattered beams, since the beam must be scanned and the depth‐dose curve must be acquired point‐by‐point.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, quenching effects may occur in regions with increased LET and therefore solid detectors must be used carefully. Diamond detectors are tissue equivalent and therefore could be of high interest in future . The microDiamond TM60019 (PTW, Freiburg), which offers an effective thickness of 1 μ m, a radius of 1.1 mm and a volume of 0.004 mm 3 , has been used for reference transverse profile acquisitions in water for TPS commissioning.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, diamond detectors have regained interest because the current manufacturing technology allows for reproducible high‐purity crystal growth. Commercially available synthetic diamond detectors microDiamond (PTW 60019, Freiburg, Germany) have been used in small‐field dosimetry of high‐energy photon and electron beams, as well as in proton and carbon beams . These studies showed that the detectors have low absorbed‐dose energy dependence, negligible dose‐rate dependence and do not require high pre‐irradiation doses (up to 2 Gy).…”
Section: Introductionmentioning
confidence: 99%